Array - Amalina, Endah Nur; Inayati, Ro'ufah (Jurnal Pendidikan Ekonomi (JUPE), 2021)
Digital technology-based learning media has not been widely used yet in SMA Negeri 1 Singosari. The economic subject learning process used by the teachers in SMA Negeri 1 Singosari, in textbooks and PowerPoint, does not maximize the facilities and potential available in this digital era, hindering students' capability in learning well. The school rules that do not prohibit students from bringing smartphones to school and the development of media and technology can minimize the obstacle. This research and development aim to develop an android game-based learning media called "Economic Monopoly (Ecopoly)" for 10th grader economic subject of SMA Negeri 1 Singosari in some chapters such as Sentral Bank, Payment Method, and Payment Tool. The study design for this research is the R&D method that refers to the ADDIE model. The developed media later will be validated by the subject expert, media expert, and the users. The final expert validation result show that Economic Monopoly (Ecopoly), referred to as "Very Worthy, " is used as an economic subject learning media for sentral bank, payment method, and payment tool.